UJI TOKSISITAS AKUT EKSTRAK BUAH OKRA (Abelmoschus esculatus L. Moench) TERHADAP PARAMETER KADAR SGOT DAN SGPT SERTA HISTOPATOLOGI HEPAR TIKUS GALUR WISTAR - Nurfatwa, Maritsa (STIKes Bakti Tunas Husada, 2018)
Okra (Abelmoschus esculatus l. Moench) fruit has been used empirically and scientifically proven to have effect to controlÂ blood cholesterol and blood glucose level. However, there has been no research on okra ethanol extract acute toxicity effect on hepatocyte. This research was aim to evaluate okra ethanol extract acute toxicity on liver using SGOT, SGPT and liver histopathology parameter after given 300 mg/kg bw (1 dose), 2000 mg/kg bw (dose 2) and 5000 mg/kg bw (3 doses) okra ethanol extract to female wistar rats. There were no significant differences on SGOT and SGPT level among all of experiment groups, but SGOT and SGPT increased along with increasing dosage. Histopathology showed no significant damage on hepatocytes. Okra ethanol extract has no acute toxic effect on the liver.Â Keywords: Okra, SGOT, SGPT, histopathology.